Recent Publications (Quarterly Journal of Economics, 1940)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 54, Issue 2, February 1940, Pages 365–368, https://doi.org/10.1093/qje/54.2.365 Published: 01 February 1940